HISTORICAL DEVELOPMENT OF STRENGTHENING THE FAMILY'S PLACE IN SOCIETY - Khursanov Omadbek (Bright Mind Publishing, 2025)
The article presents ideas on the preservation of the family as a part of society, the historical development of the family and marriage in the period of primitive historical development.
Keywords: Family, marriage, consciousness, knowledge, man, history, development, society, time, primitive, cultural, heritage, enlightenment, thought, prehistory, psychoanalytic.